Learning lessons from the 2011 Van Earthquake to enhance healthcare surge capacity in Turkey. (2nd January 2016) - Achour, Nebil; Pascale, Federica; Price, Andrew D. F.; Polverino, Francesco; Aciksari, Kurtulus; Miyajima, Masakatsu; Özüçelik, Dogac Niyazi; Yoshida, Masaho
ABSTRACT: Historically, Turkey has adopted a reactive approach to natural hazards which resulted in significant losses. However, following the 1999 Kocaeli Earthquake, a more proactive approach has been adopted. This study aims to explore the way this new approach operates on the ground. A multinational and multidisciplinary team conducted a field investigation following the 2011 Van Earthquake to identify lessons to inform healthcare emergency planning in Turkey and elsewhere. The team interviewed selected stakeholders including, healthcare emergency responders, search and rescue services, ambulance services, and health authority representatives, in addition to conducting a focus group. Data were analysed according to an open coding process and SWOT (strength, weakness, opportunity, and threat) analysis. The findings suggest that the approach succeeded in developing a single vision by consolidating official efforts in a more structured way, mobilising many governmental and non-governmental organisations, securing significant amounts of resources including physical and human, and increasing the resilience and flexibility of infrastructure to expand its capacity. However, more attention is required to the development of stronger management procedures and acquisition of further resources.